Active nanoplasmonic metamaterials - Hess,O; Pendry,JB; Maier,SA; Oulton,RF; Hamm,JM; Tsakmakidis,KL (Nature Materials, 2012)
Optical metamaterials and nanoplasmonics bridge the gap between conventional optics and the nanoworld. Exciting and technologically important capabilities range from subwavelength focusing and stopped light to invisibility cloaking, with applications across science and engineering from biophotonics to nanocircuitry. A problem that has hampered practical imple- mentations have been dissipative metal losses, but the efficient use of optical gain has been shown to compensate these and to allow for loss-free operation, amplification and nanoscopic lasing. Here, we review recent and ongoing progress in the realm of active, gain-enhanced nanoplasmonic metamaterials. On introducing and expounding the underlying theoretical concepts of the complex interaction between plasmons and gain media, we examine the experimental efforts in areas such as nano- plasmonic and metamaterial lasers. We underscore important current trends that may lead to improved active imaging, ultra- fast nonlinearities on the nanoscale or cavity-free lasing in the stopped-light regime.